The neuromyelitis optica spectrum disorders: approaches for problem resolution in medical rehabilitation - V. S. Krasnov; V. D. Piven; N. A. Totolyan; A. A. Gotovchikov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The necessity of search of the effective individual programs for rehabilitation in patients with neuromyelitis optica spectrum disorders (NMOSDs) is recognized by majority of authors. Clinical and laboratory features of these patients which could impact on the rehabilitation prognosis were provided in this article. The possible methods for evaluation of the neurological deficit and disability because of NMOSDs were described. The literature data devoted to priority tasks of rehabilitation programs for this category of patients were given.